Investigation of World assumption, personal attributes and gender roles of adolescents - SERT, MERAL (E D P SCIENCES, 2018)
This research aims to examine adolescents' world assumptions, personal attributes and gender roles. The research has attempted to examine the thoughts of adolescents about the world and the ways in which they define themselves as a man or a woman by considering the fact that their lives are affected not only by traumatic events but also by several family and environmental dynamics affecting their quality of life. Data was obtained from randomly selected 407 high school students from Kadikoy district in Istanbul province, by applying World Assumptions Scale (WAS), Extended Personal Attributes Questionnaire (EPAQ), Gender Roles Attitude Scale (GRAS), and Data Collection Form. Our results showed that there was a significant difference in the scales and subdimensions used in the research with respect to gender, grade, family characteristics as well as life standards, balance of standards, adequacy of/change in family income, living with the family without problems, level of satisfaction with the environment, and the desire to change the living environment. In addition to a positive relationship between world assumptions and personal attributes, various correlations in different directions were also found between the sub-dimensions of the scales. Our research has shown that adolescents' life dynamics can make a difference in their perception of the world and their assumptions about perceiving themselves as moral and valuable individuals, as well as their personal attributes and perceptions about gender roles.
Keywords: World assumptions; personal attributes; gender roles; quality of life; adolescence; gender identity and sex role behaviors; QUALITY-OF-LIFE; STRESS; VALIDITY